Overview of teaching psychology at Lithuanian schools in the late 17th century - early 18th century - Plečkaitis, R. (Psichologija, 1962)
The topic of teaching scholastic psychology in Lithuania is discussed. It was not an independent discipline of philosophy and was treated as a separate tractate of physics or nature philosophy under the title “On the Soul” (“De anima”). Under the effect of the authoritarian principle, the aforementioned essay explained and commented Aristotle’s “On the Soul.” However, based on authorities of the Middle Ages on the one hand, such as Albert the Great, Thomas Aquinas, and Duns Scotus, and scholastic celebrities of the 16th-17th centuries on the other hand, eclecticism prevailed that tried to unite viewpoints of different authorities. Instruction on psychological teachings by the New Ages philosophy authors was forbidden, although some ideas of these authors were sometimes discussed; however, their names were not mentioned. Thus, Descartes’ understanding of a reflex was not alien to psychology taught in the old academy of Vilnius during the second half of 17th century. The main concept of scholastic psychology was the concept of the soul which, according to Aristotle, was divided into the nourishing, feeling, and thinking. In some courses we find a clear trend to explain psychic phenomena by associating them with material processes taking place in a human body. A decisive role of the brain is emphasized and an idea is raised about the localization of psychic processes in the brain. The scholastic psychology went beyond the framework of Aristotle’s work by raising and solving new problems, e.g. relationship between language and thinking. A theory on the will has been well developed. A book “Theoremata philosophica” by the Lithuanian I. Kimbaras issued in Grace in 1600 is worthy of attention. Scholastic psychology in Lithuania may not be treated as something homogenous, void of internal disparities.